Towards detection of atrazine and 2,4,6-TCP in wine and other matrices - Dumont, Christopher (Cranfield University, 2007)
GOODFOOD aimed to develop new generation micro- and nanoscale devices for safety and quality assurance in the food chain and agrofood industry. Cranfield University, along with other partners in Worpackage 2, was responsible for developing immunosensors for the determination of pesticides in wines and fruit juices at analytically valid levels. Methods and Materials The immunosensor format was based on the use of antibodies with binding specificity directed towards the target analytes. These were chiefly supplied by CSIC in Barcelona. The protocol and reagents supplied were used for detection of atrazine and 2,4,6-Trichlorophenol in various matrices. Screen Printed Electrodes were produced, comprising carbon working and counter electrodes and Ag/AgCl working electrode. Screen printed electrodes can be mass-produced at low cost, and so are disposable after a single use. A macro-scale flow-cell system was used with the screen-printed electrodes for detection of horseradish peroxide (HRP) which is the enzyme label for the assay (Figure 3). As part of system optimisation, three electron acceptors were compared. Reaction time between substrate and enzyme was also examined as a factor. As a step towards miniaturisation, HRP was immobilised onto magnetic beads and then dilutions of the beads were measured in order to help calibrate the system. Activated Sepharose 4B TM from Pharmacia was also used as a solid support. Small-scale Polydimethylsiloxane (PDMS) and adhesive-layer cells Dumont / DETECTION OF PESTICIDES iv were manufactured for optical analysis of immunoassay product. Optical analysis was performed by an RGB reader developed in-house. Results The detection of atrazine and 2,4,6-TCP at nanomolar concentrations in various matrices, using the supplied reagents was demonstrated. Of the three electron acceptors tested, ABTS was found to be most effective. Increased reaction time was found to increase the signal. Dilutions of magnetic beads coated with immobilised HRP gave a proportional response as anticipated. Data obtained by optical analysis of assay product using the RGB- reader followed the expected trend and showed signal intensity reduction with increasing analyte concentration.